Evaluation of the Influence of Profitability and Financial Performance on Stock Price - Lumempow, Valentino (KINERJA: Jurnal Manajemen Organisasi dan Industri, 2023)
To achieve the goal of realizing transparency and accountability of financial information, every company that is to be published is required to submit annual financial reports to the Indonesia Stock Exchange and to investors. This study aims to determine the effect of financial performance variables on profitability and its impact on stock prices in the Property sector and companies Real Estate listed on the Malaysia Stock Exchange in 2010-2015. The sample used is secondary data from the Malaysian Stock Exchange. Samples were taken by method purposive sampling, and there are 5 companies that meet the sample selection criteria. Statistical tests were carried out using the panel data regression test random effect. The research results show that partially Current Ratio No significant effect on Return on Asset. However Total Asset Turnover and Debt Ratio positive and significant effect on Return on Asset. Simultaneously variable Current Ratio, Total Asset Turnover and Debt Ratio significant effect on Return on Asset. Return on Asset also does not have a significant impact on the share price.